Association Between Benzodiazepine and Opioid Prescription and Mortality Among Patients in a Large Healthcare System. Issue 1 (January 2022) - Mooney, Larissa J.; Zhu, Yuhui; Yoo, Caroline K.; Wolitzky-Taylor, Kate; Hser, Yih-Ing
Abstract : Objective: Coprescription of opioids and benzodiazepines (BDZ) is associated with adverse outcomes, including greater healthcare utilization and overdose risk. This study aims to examine opioid and BDZ coprescription, dosing, and mortality among patients with and without opioid use disorder (OUD) in a large healthcare system. Methods: Using data from the California state Prescription Drug Monitoring Program during 2010 to 2014 linked with a large healthcare system electronic health record database and mortality records from the Centers for Disease Control National Death Index, this study examined 5202 patients (1978 with OUD, 3224 controls). Multiple logistic regression analyses were conducted to examine relationships between most recent BDZ and opioid prescription, and their interaction with respect to mortality. Results: About 10.5% of the sample died on or before December 31, 2014. About 17.7% were prescribed BDZ during the final month of observation. Individuals with OUD were prescribed higher average BDZ and opioid doses than those without OUD. After adjusting for covariates, increased prescribed doses of BDZ (odds ratio [OR]=1.34, 95%CI: 1.15–1.55 per 10 mg/d increment) and opioids (OR = 1.04, 95%CI: 1.02–1.05 per 10 mg/d increment) were positively associated with mortality. Non-OUD patients who received both BDZ and opioid prescriptions had a higher mortality than those who received only BDZ or opioids (The ratio of odds ratio (ROR) = 3.83, 95%CI: 1.78–8.21). Conclusions: Study findings highlight significant mortality associated with the coprescription of opioids and BDZ in a general healthcare setting. Further research is needed to elucidate factors associated with mortality among non-OUD patients who are co-prescribed opioids and BDZ. Abstract : Supplemental Digital Content is available in the text